Offline programming for peening of complex geometry - Chua, Aldrich Yu Han (2019)
With rapid technological advancement, components continue to evolve to become more complex to reduce weight and increase efficiencies. An example of such complex components is a Blisk, which has increased demands due to providing higher efficiencies in aircraft engines. There is a Blisk caliper nozzle available in the market to shot peen the Blisk airfoils to provide even and uniform peening, but there is insufficient information on how to use it. Also, the shot peening team in ARTC looks to broaden their capabilities to peen complex components after conducting many in depth process-related work. Taking on this project will reduce reliance on external teams for help and create more visibility and business opportunities with member companies. Therefore, this project focuses on the method development of using the Blisk caliper nozzle to peen Blisk airfoils. This includes designing and fabrication of fixtures, robot programming and testing of program. This is later verified by peening saturation curves on the shot peening machine in ARTC. It was found out that offline robot programming relied not only on the CAD model provided by the vendor, but also verifying the actual dimensions on the actual equipment or fabricated fixtures. The verification conducted found out that the actual dimension in the shot peening machine did not match the CAD model, and the fabricated fixtures were out of dimensions even though CAD model is provided to the vendors, causing the offline program to not work as desired. Also, it was also noticed that offline robot programming is most suitable for complex features like airfoils, but not for simple geometry like Almen strip peening.